An empirical Investigation of the Nexus between Disclosure level and Financial Performance on Ethiopian Commercial Banks: A Simultaneous Equations Approach - Kefale, Degu; Malhotra, Keshav; Aggarwal, Monika (Gyan Management Journal, 2023)
The study aimed to examine the effect of disclosure on bank financial  performance and the simultaneous relationship between them. To  achieve the objective six-year secondary data was collected from  seventeen Ethiopian commercial banks. To examine the effect of  disclosure on financial performance and its simultaneous association  with financial performance 3SLS (three-stage least square) regression  was employed. The 3SLS estimation output indicated that financial  disclosure has a significant effect on bank financial performance  regardless of the proxies used to measure financial performance.  Whereas social disclosure has a significant effect on return on equity  and net interest margin. Regarding the simultaneous relationship  between disclosure and financial performance; financial disclosure has  a significant mutual association with all financial performance measures  used in this study. However social disclosure level has a significant  interdependent association only with net interest margin. From the  estimation output bank managers can recommend that disclosure level  and financial performance are interdependent variables that should be  scrutinized to maximize their performance level.
Keywords: Bank; Financial Performance; inancial Disclosure; Social Disclosure; 3SLS; Ethiopia